2020
DOI: 10.1039/c9ra10826b
|View full text |Cite
|
Sign up to set email alerts
|

Development of high-performance mixed matrix reverse osmosis membranes by incorporating aminosilane-modified hydrotalcite

Abstract: Thin film nanocomposite reverse osmosis membranes were prepared by dispersing 3-aminopropyltriethoxysilane modified hydrotalcite in aqueous solution and incorporating the nanoparticles in polyamide layer during interfacial polymerization process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…A rich variety of novel materials varied in their dimensions, structure, and functionalities have been engineered to render the desired properties for TFC membrane modifications, which led to a subclass of membranes known as thin-film nanocomposite (TFN). The nanomaterials can be feasibly introduced to the TFC through approaches such as direct dispersion during interfacial polymerization, [91][92][93][94] layer-by-layer assembly, [95,96] in situ assembly, [97] and grafting. [98] Characterized by their astonishing mechanical properties, some of these high-strength nanomaterials have also been explored as the free-standing or self-supporting ultrathin membranes.…”
Section: Membrane Developmentmentioning
confidence: 99%
“…A rich variety of novel materials varied in their dimensions, structure, and functionalities have been engineered to render the desired properties for TFC membrane modifications, which led to a subclass of membranes known as thin-film nanocomposite (TFN). The nanomaterials can be feasibly introduced to the TFC through approaches such as direct dispersion during interfacial polymerization, [91][92][93][94] layer-by-layer assembly, [95,96] in situ assembly, [97] and grafting. [98] Characterized by their astonishing mechanical properties, some of these high-strength nanomaterials have also been explored as the free-standing or self-supporting ultrathin membranes.…”
Section: Membrane Developmentmentioning
confidence: 99%
“…The membrane processes for the reverse osmosis (RO) technology using one of the membranes welding in terms of driving force are high pressure thrust, as well as microfiltration (MF), ultrafiltration (UF), and piezodialysis [ 17 ]. Membrane performance in RO systems is the top choice by the water-treatment industry leaders due to low-energy consumption; application under normal conditions; ease to be combined (hybridized) with other operations; requiring no optional additives; simple and compact membrane module design specifications; and ease of utilizing in its operation [ 18 , 19 ]. For example, two studies by Zhang [ 20 , 21 ] reported that the use of rotating graphene nanoporous membranes with pores of diameter 2 to 4 nanometers successfully performed almost 100% salt rejection by using the RO system.…”
Section: Ro Membranes In Desalination Technologies and Their Novelmentioning
confidence: 99%